Optimización conjunta de la gestión de la movilidad y la capacidad en redes 5G - Ramírez-Arroyo, Alejandro; Valenzuela-Valdés, Juan Francisco; Carmona Murillo, Javier; Luna-Valero, Francisco; Valenzuela Valdés, Antonio; Padilla-de-la-Torre, Pablo (My University, 2019)
Technology development is needed to meet users' traffic demands. From 2017 to 2022, global annual traffic growth is estimated at 220%. This annual growth leads in turn to an increase in the number of users connected to IP networks, going from 2.4 to 3.6 devices connected per person. These data show the importance of developing an infrastructure where this traffic can be maintained. Currently, 4G networks are capable of handling this load. However, the need for the emergence of 5G networks in a short period of time, which is expected by 2020, is visible. On the other hand, it is mandatory to reduce the power consumption by telecommunication industry. In this work, a preliminary study of the optimisation of various parameters of the 5G system is presented. It presents the configuration of the different basic parameters of the system, describes the different assignment plans of each user to each of the base stations and optimizes the power transmitted by the base stations to obtain simultaneous improvements in system capacity, overall consumption of base stations and the cost of signaling in different mobility protocols. In other words, for the first time a joint optimisation for several network levels is presented.
Keywords: Telefonía móvil; 5G; Movilidad; Mejora de la capacidad; Optimización